Answer:
Step-by-step explanation:
x-y=11
2x+y=19
---------------
x=y+11
2(y+11)+y=19
2y+22+y=19
3y+22=19
3y=19-22
3y=-3
y=-3/3
y=-1
x-(-1)=11
x+1=11
x=11-1
x=10
Answer: x=10, y=-1. (10, -1).
-----------------------------------------
-6x+5y=1
6x+4y=-10
-------------------
9y=-9
y=-9/9
y=-1
6x+4(-1)=-10
6x-4=-10
6x=-10+4
6x=-6
x=-6/6
x=-1
Answer: x=-1, y=-1. (-1, -1).
------------------------------------
2x+9y=25
-4x-9y=-23
-------------------
-2x=2
x=2/-2
x=-1
2(-1)+9y=25
-2+9y=25
9y=25-(-2)
9y=25+2
9y=27
y=27/9
y=3
Answer: x=-1, y=3. (-1, 3).
Answer:
3x = 2(-3x + 1)
Step-by-step explanation:
I think that's it I think it could be wrong but I tried
Answer: x=3
Step-by-step explanation: First we do distributive property in the parentheses. Next we subtract both sides by 6. Lastly we divide both sides by 3. Algebraic Rules!!!
Work:
3(x+2)=15
3x+6=15
3x+6-6=15-6
3x=9
3x/3=9/3
x=3
Answer:
x=12
Step-by-step explanation:
tangent forms 90° with the touch point at circle
(x+8)^2 = 256+x^2
x^2 + 16x + 64 = 256 + x^2
16x = 192
x= 12
Answer:
48
Step-by-step explanation:
120 divided by 2.5 = 40